ANALISIS KARAKTER DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 7 SMP NEGERI 1 PARANGINAN - Elda kertiasa Sihombing (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2023)
The purpose of this study was to analyze the influence of student character and student learning interest on the mathematics learning outcomes of Grade 7 students at SMP Negeri 1 Paranginan, Humbang Hasundutan district. This study uses a quantitative approach with a survey method with a causal approach. The research sample was taken by 30 respondents. The findings obtained from this study are: 1) Student character has a positive effect on mathematics learning outcomes for Grade 7 students at SMP Negeri 1 Paranginan, Humbang Hasundutan district. This means that a positive student attitude in learning will lead to good learning outcomes, 2) Learning interest has a positive effect on Mathematics learning outcomes for Grade 7 students of SMP Negeri 1 Paranginan, Humbang Hasundutan district. This means that students' interest in learning will lead to good learning outcomes, 3) Student attitudes have a positive effect on interest in learning Mathematics for Grade 7 students of SMP Negeri 1 Paranginan, Humbang Hasundutan district.